2012
DOI: 10.1007/s10719-012-9460-8
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-based analysis of fucose and sialic acid expressions on human amniotic IgA during normal pregnancy

Abstract: The sugar moiety of IgA is known to provide a link between the innate and adaptive immune systems. Terminally located glycotopes on IgA are potential ligands engaged in the interactions which may modulate the biological activities of IgA. In the present work the expressions of Maackia amurensis (MAA), Sambucus nigra (SNA), Lens culinaris (LCA), Tetragonolobus purpureus (LTA), and Ulex europaeus (UEA) reactive glycotopes on maternal plasma and amniotic IgA were evaluated in relation to the progression of a norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
2
8
1
Order By: Relevance
“…Obtained results indicated differences in the expression of mono/polysialylated as well as of O-acetylated species in the two ganglioside mixtures which support earlier hypothesis regarding the direct correlation between the sialylation and acetylation degree and brain developmental stage: a higher sialylation degree being specific for incipient developmental stages while a higher acetylation for more developed brains. Our findings are in agreement with the results of Orczyk-Pawiłowicz et al [37] who have studied the amniotic IgA structure during the same gestational stage i.e. the second trimester.…”
Section: Resultssupporting
confidence: 93%
“…Obtained results indicated differences in the expression of mono/polysialylated as well as of O-acetylated species in the two ganglioside mixtures which support earlier hypothesis regarding the direct correlation between the sialylation and acetylation degree and brain developmental stage: a higher sialylation degree being specific for incipient developmental stages while a higher acetylation for more developed brains. Our findings are in agreement with the results of Orczyk-Pawiłowicz et al [37] who have studied the amniotic IgA structure during the same gestational stage i.e. the second trimester.…”
Section: Resultssupporting
confidence: 93%
“…Sialic acids on N -glycans of the standard serum IgA samples analysed in this study were almost exclusively α2,6-linked (>95%), which is in line with previous reports41025. With regard to the level of sialylation of N -glycans, Orczyk-Pawilowicz et al .…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the level of sialylation of N -glycans, Orczyk-Pawilowicz et al . reported no significant changes after delivery25. However, in the current study we have found that sialylation levels at Asn144 were lower after delivery.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The results were calculated using BD CellQuest software and expressed in cells/µl. Immunoglobulin level: Antibodies are capable of binding antigens with a high affinity and contribute to their effective elimination by various mechanisms that are activated by the complex antigen‐antibody. The main functions of antibodies include complement activation, opsonization and activation effector cells such as phagocytic cells, T cells, NK cells.Total IgA and IgG levels were measured in a participant's serum by the enzyme‐linked immunosorbent assay (ELISA) using previously calibrated reagents and a panel of serum‐sample dilutions (according to methods described by Orczyk‐Pawiłowicz et al, ). The absorbance was measured using a spectrophotometer (Asys UVM340, Biochrom).…”
Section: Methodsmentioning
confidence: 99%